ASSESSMENT OF THE BENEFITS OF TAKING HERBAL MEDICINES AND SUPPLEMENTS TO OVERCOME THE SYMPTOMS OF MENOPAUSE - Neli Ermenlieva; Krasimira Laleva; Yordanka Mihaylova; Emilia Georgieva; Tsvetelina Popova (Peytchinski Publishing, 2018)
In recent years, there is a trend towards increasing consumption of natural therapeutic agents to manage the symptoms of menopause. Common ingredients in natural preparations include Cranberry extract, Oenotherabiennis oil, Glycine max, Cimicifuga racemose extract, and others. They improve the physical and emotional health of menopausal women and help to overcome hormonal imbalance. The study is conducted on the territory of Varna Municipality through a direct anonymous inquiry during the period January - March 2018. The study included 50 female respondents (n=50) with menopausal symptoms, between the age of 35 and 65 years. The study results demonstrated the increase in consumption of natural preparations for managing menopausal symptoms (86% of respondents). The herbal product and/or nutrition supplement that respondents take contain mostly calcium in combination with vitamin D, cranberry extract and evening primrose oil. To a lower extent, female respondents take preparations which contain soy phytoestrogens or silver candle herb. A big relative share of respondents (76%) reported for significant improvement in their health condition. There is a positive correlation between this indicator and the longer period of natural product intake. Regarding the subjective assessment of respondents about the price of the natural product they use, 74% of women claim that they can afford it. There is no direct relationship between the monthly income of respondents and the way they define the price.